Epilepsy Did it Again: Memory and Model-Based Planning Studied in Patients After Epilepsy Surgery. Issue 4 (July 2019) - Velíšek, Libor
Hippocampal Contributions to Model-Based Planning and Spatial Memory. Vikbladh OM, Meager MR, King J, et al. Neuron. 2019;102:1-11. pii: S0896-6273(19)30123-0. doi: 10.1016/j.neuron.2019.02.014. [Epub ahead of print] PMID: 30871859 Little is known about the neural mechanisms that allow humans and animals to plan actions using knowledge of task contingencies. Emerging theories hypothesize that it involves the same hippocampal mechanisms that support self-localization and memory for locations. Yet limited direct evidence supports the link between planning and the hippocampal place map. We addressed this by investigating model-based planning and place memory in healthy controls and patients with epilepsy treated using unilateral anterior temporal lobectomy with hippocampal resection. Both functions were impaired in the patient group. Specifically, the planning impairment was related to right hippocampal lesion size, controlling for overall lesion size. Furthermore, although planning and boundary-driven place memory covaried in the control group, this relationship was attenuated in patients, consistent with both functions relying on the same structure in the healthy brain. These findings clarify both the neural mechanism of model-based planning and the scope of hippocampal contributions to behavior.